Pengaruh service quality, trust, customer satisfaction, terhadap customer loyalty nasabah bank mandiri di Surabaya - Farah Alya Abidah; Rachmat, Basuki (Universitas Hayam Wuruk Perbanas, 2025)
This study analyses the effect of service quality, trust, and customer satisfaction on Bank Mandiri customer loyalty in Surabaya City. The main objective is to identify the challenges of meeting increasing customer expectations, and several incidents affect customer trust in banks, such as data breaches and unsatisfactory service. This research uses a quantitative method with a descriptive approach, with data obtained through a survey of 363 respondents and analyzed using SmartPLS 3.0. The results showed that service quality significantly impacts customer trust, satisfaction, and loyalty, with trust and satisfaction also increasing customer loyalty. The results of this study highlight the importance of implementing high-quality services that include tangible, reliability, responsiveness, empathy, and assurance elements. The implications of this study suggest that Bank Mandiri needs to provide training to employees to improve the quality of interactions as well as create more innovative customer loyalty programs and ensure the security of customer data by developing a high-tech security system. These efforts are critical to maintaining customer trust and fostering a stronger long-term relationship between Bank Mandiri and its customers.